Pengaruh Kualitas Produk dan Promosi terhadap Minat Beli Perumahan Kenten Resort Palembang - Mutiara, Fatiah; Megawati, Megawati (Publikasi Riset Mahasiswa Manajemen, 2023)
Determinants of Buying Interest Factors are Product Quality, Brand, Price, and Promotion. This study aims to test whether product quality, brand, price, and promotion have a mutual effect on buying interest in Kenten Resort Palembang housing. Using causal quantitative methods and with a sample of 144 respondents. The data analysis method used no-probability sampling, as well as multiple regression with the SPSS ver- sion 26 statistical test tool. Based on the results of the study, it was shown that the vari- ables of Product Quality, Brand, Price, and Promotion had a significant and positive ef- fect on Buying Interest for Kenten Resort Palembang Housing